Correlation Between Vertical Wheel Impact Energy With Lateral Wheel Impact Energy : A Finite Element Analysis Approach - Zainuddin, Hidayat; Ali, Mohd Basri; Muhammad Said, Nurlaela; Zakaria, Kamarul Ariffin (UMP Publisher, 2016)
-